Analisis Strategi Public Relations Teater Koma dalam Menjaga Minat Penonton Selama Pandemi Covid-19 - Sebastian, Dick Perthino; Widodo, Eko (Jurnal InterAct, 2023)
The pandemic had a significant impact on show business. Many institutions must change, innovate, and adapt to be able to adjust to the changes that occur and still be able to grow and develop. This research was conducted to explore Teater Koma's public relations strategy for maintaining audience interest during the Covid-19 pandemic. The analytical framework used in viewing the public relations strategy of Teater Kota uses the framework developed by Ronald D. Smith, which includes the stages of Formative Research, Strategy, Tactics, and Evaluative Research. The research was conducted by conducting in-depth interviews with the management of Teater Koma during the pandemic. During the pandemic, Teater Koma maintained the interest of its audience by changing the show format to various online programs. The communication measures implemented were able to keep the loyal audience of Teater Koma to see the variety of entertainment programs.